1996
DOI: 10.1021/ma951194j
|View full text |Cite
|
Sign up to set email alerts
|

Analogy between Swelling of Gels and Intrinsic Viscosity of Polymer Solutions for Ion-Complexed Poly(vinyl alcohol) in Aqueous Medium

Abstract: The swelling/shrinking behavior of chemically cross-linked poly(vinyl alcohol) (PVA) gel complexed with borate ions in aqueous medium and the intrinsic viscosity behavior of the corresponding polymer solutions were compared as a function of the boric acid concentration, b. The equilibrium swelling ratio of the gels, Q/Q 0, and the intrinsic viscosity ratio of the solutions, [η]/[η]0, were in good accordance when the NaOH concentration, [NaOH], is high enough, where Q 0 and [η]0 are the equilibrium swelling vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…This shear thinning behavior observed at high frequency is ascribed to the occurrence of a shear‐induced phase separation. The phase separation condition of the polymer solutions were determined by monitoring the sharp drop of measured viscosity during the increase of frequency 11, 14, 20. However, a different behavior was observed for the PVA‐13 solution, which exhibited almost Newtonian character over the frequency range examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shear thinning behavior observed at high frequency is ascribed to the occurrence of a shear‐induced phase separation. The phase separation condition of the polymer solutions were determined by monitoring the sharp drop of measured viscosity during the increase of frequency 11, 14, 20. However, a different behavior was observed for the PVA‐13 solution, which exhibited almost Newtonian character over the frequency range examined.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the mechanical properties of PVA solutions are highly dependent on the formation of inter‐ or intra‐molecular hydrogen bonds between OH groups. Moreover, inter‐ or intra‐molecular hydrogen bonding may bring about complicated phenomena such as phase separation and gelation, which means the solution properties exhibit time‐dependence 8–11. However, the relationships between the bonding and these phenomena have not yet been discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained from the earlier investigated interpolymer complex of the linear polymers 14,16) showed that the organic solvent dimethyl sulfoxide is responsible for both the destruction of the hydrogen bonds and decreasing hydrophobic interactions. Taking into account an analogy of the one-to-one correspondence in the size of a single polymer chain in solution with that of subchain in a network 18) one can expect the same behaviour of both the K S and the intrinsic viscosity [g] of the corresponding complexes. The dependences of K S of 1a -2 complexes and of [g] of 1 -2 complexes on water/dimethyl sulfoxide compositions are presented in Fig.…”
Section: Influence Of Water/dimethyl Sulfoxide Compositions On the Bementioning
confidence: 99%
“…[27][28][29][30] When mechanically constrained, responsive hydrogels exert swelling forces on the constraining structures. A hydrogel's response may be continuous or discrete, depending on the nature of the hydrogel and the applied stimulus.…”
Section: Introductionmentioning
confidence: 99%